Is there a Language Academy in Croatia? - Peti-Stantić, Anita (2011)
The author addresses the issue of whether three separate institutions can be treated as language academy and These institutions are HAZU, the Institute for the Croatian Language and Linguistics and the Council for the Norms of the Croatian Standard Language. Although three primary institutions engaged in language management activities in Croatia today, rather than a single “language academy” constituted along the lines of classical models such as the Académie française are identified, the author argues that this makes little practical difference in the case of Croatia. Since it is a small country with only a limited number of people who are professionally concerned with the standard language in some way, the separation between these three bodies is far from complete. HAZU, the Council for the Norms of the Croatian Standard Language, and the Institute for the Croatian Language and Linguistics are all concerned with the status and norms of the standard language, like traditional language academies, and act in concert even though they are formally separate institutions. They are functionally equivalent to a language academy and can be considered to represent a Croatian language academy in everything but their names.